Mahmoud Darwish - Cohen-Mor, Dalya. author. aut Link
XI, 105 p. 1 illus.
Keywords: Mahmoud Darwish: Palestine’s Poet and the Other as the Beloved focuses on Palestinian national poet Mahmoud Darwish (1941–2008), whose poetry has helped to shape Palestinian identity and foster Palestinian culture through many decades of the Israeli-Palestinian conflict. Dalya Cohen-Mor explores the poet’s romantic relationship with “Rita,” an Israeli Jewish woman whom he had met in Haifa in his early twenties and to whom he had dedicated a series of love poems and prose passages, among them the iconic poem “Rita and the Gun.” Interwoven with biographical details and diverse documentary materials, this exploration reveals a fascinating facet in the poet’s personality, his self-definition, and his attitude toward the Israeli other. Comprising a close reading of Darwish’s love poems, coupled with many examples of novels and short stories from both Arabic and Hebrew fiction that deal with Arab-Jewish love stories, this book delves into the complexity of Arab-Jewish relations and shows how romance can blossom across ethno-religious lines and how politics all too often destroys it. .